Identifikasi Karakteristik Lahan Tanaman Gandaria (Bouea macrophylla Griff) Di Desa Hunuth Kecamatan Baguala Kota Ambon - Herlina N Taihuttu (Agrologia, 2013)
Gandaria (Bouea macrophylla Griff) is well-known as one of native typical fruits in Mollucas which needs to be preserved and continuously cultivated because of economical and ecological significances. Hunuth is well-known as a production centre of gandaria in Ambon. The research aimed to identify the characteristics land of gandaria. The research was done from March to May 2012 using survey and interview method. The result showed that gandaria in the research location was well adapted. Altitude is from 1 to 36 above sea level (a.s.l). Topography is from slightly tilted/wavy to slightly step. Based on climate classification by Schmidth and Fergusson, climate type of research location was in B (wet) region with the amount of annual rainfall 3030.10 mm on average. Temperature at average 14.87 to 22.29 oC , humidity on average 55.30 to 68.18 % and sun photoperiod on average  18.52 to 50.17 percent. The dominant soil type in research location were Alluvial and Cambisol.